Julio A. Roca and the “Conquest of the Desert”: monumentalization, heritage and past uses during the 1930s and 1940s (Quinto Sol, 2018)
The image of the “Conquest of the Desert” as one of the founding episodes of the Argentine State and of Julio A. Roca as its main architect was built at the end of the 19th century. During the conservative governments of the Concordancia (1932-1943) indeed monuments were erected to the former president and the places linked to that episode were declared “historic”. This article explores these actions as historiographic operations deployed by such governments. For this purpose, the activities carried out by the “Comisión Nacional Monumento al Teniente General Roca” and by the Comisión Nacional de Museos y de Monumentos y Lugares Históricos are analyzed. Thus, the past was instrumentalized by the conservative governments with the purpose of inscribing themselves in the late-century liberal tradition and presenting themselves as their continuity after what they considered the “deviation” of the presidencies of the Unión Cívica Radical, especially from Hipólito Yrigoyen’s term.
Keywords: Conquest of the Desert; Julio A. Roca; commemorations; uses of the past